L’emergenza orfani nella grande guerra e la magistratura (Italian Review of Legal History, 2017)
The formidably complex problem of World War I orphans can be studied from different points of view, ranging from moral, family and social aspects to those of a legal, economic, political or financial nature. In this short essay, only some of these facets are considered. Among the measures taken by the Italian authorities – first by the government as a matter of urgency, and later by the parliament – attention is focused on the role of the judiciary and especially on the giudice delle tutele, or guardianship judge. He performed delicate tasks of voluntary jurisdiction and supervised the actions of the pretori (local magistrates). He also contributed to various administrative activities, as he was a member of the Provincial Committee in charge of providing assistance to war orphans. He acted as a coordinator on several fronts, and in particular, he had to find the right balance between the actions of the State and those of the family. Indeed, he had to ensure – in keeping with the intention of legislators – that the State did not interfere with and replace families, but simply stepped in to support them when necessary.
Keywords: War orphans; World War I; Judiciary; Guardianship Judge; Natural Paternity